Legal Implications of the Constitutional Court Decision Number 60/PUU-XXII/2024 on the Simultaneous Regional Head Elections in 2024 - Priyanto, Ari; Al arif, M.Yasin (Jurnal Ius Constituendum, 2025)
The purpose of this study is to analyze the legal implications of the Constitutional Court's decision Number 60/PUU-XXII/2024 on the simultaneous regional head elections in 2024. Recently, the Constitutional Court issued Decision Number 60/PUU-XXII/2024, which is a test of Article 40 paragraph (3) of Law Number 10/2016 on the election of Governors, Regents, and Mayors against the 1945 Constitution of the Republic of Indonesia, which was submitted by the Labour Party and Gelora. This research is normative juridical research. The approaches used include the conceptual approach, statute approach, and case approach. Covering primary, secondary, and tertiary legal materials. The results of this study concluded that Decision Number 60/PUU-XXII/2024 juridically and sociologically has implications for the simultaneous regional elections in 2024. There are direct and indirect implications, directly with the formation of a new PKPU, namely Number 10 of 2024 as the basis for holding simultaneous elections in 2024, and indirect implications such as strengthening local democracy, strengthening political parties, and Constitutional Court Decision Number 60/PUU-XXII/2024 indirectly setting a precedent for Decision Number 62/PUU-XXII/2024 regarding the elimination of the presidential threshold. This research can contribute to changes in regulations or technical regulations that must be made by the General Elections Commission (KPU) and the government after the Constitutional Court's decision and provide recommendations to policymakers in designing regulations by the Constitutional Court's decision. In addition, it contributes to the development of the theory of democracy and elections, especially related to the principles of free and fair elections and electoral justice.